Monitoring Therapeutic Side Effects (carcinogenic and non-carcinogenic) with Linked Cancer Registry Data in Australia - Roder, David; Buckley, Elizabeth (Asian Pacific Journal of Environment and Cancer, 2021)
Population-based cancer registries (PBCRs) continue to have a crucial role in surveillance of cancer incidence, mortality, survival and prevalence in different countries. The International Agency for Research on Cancer has used PBCR data as its principal touchstone for estimating cancer and cancer mortality risk worldwide and by country. PBCRs have provided evidence for service planning, evaluation, and quality improvement, and population health and health system research. Increasingly they are being used as a spine for linking data from other databases relating to primary prevention initiatives, screening, treatment provision, and the delivery of support services. PBCRs have long been used in investigations of environmental hazards, as applying for example to exposures to radon, asbestos dust, and agricultural chemicals. The required data for these investigations are generally not available from PBCRs as a one-stop data source, but from PBCRs supplemented with data on exposures collected through surveys, industry records, and increasingly, from linked databases. Cancer survival has increased markedly in economically developed countries in through advances in surgery, radiotherapy, and systemic therapies. The net gains have often been impressive but adverse effects are occurring. New chemotherapy and other systemic therapies can be associated with carcinogenesis and other adverse effects on cardiac and other vital organs. These effects may not be detected until extensive latency periods have passed. An important role of linked datasets is to flag possible adverse effects, their potential scale, and population distribution, and to indicate where further research is warranted. This report discusses the use of PBCRs in monitoring carcinogenic and noncarcinogenic side effects, and the role of data linkage as an enabler. The opportunities to use PBCRs for this purpose depend on their availability, access to relevant disease registries, administrative data, and death data. Opportunities would also vary depending on competing priorities and availability of an enabling legal framework.